The Key To Successfully Navigating The Career World: Perspectives From Holland, Super and Krumboltz Theories - Laela, Faizah Noer; Amriana, Amriana; Rokhma, Lailatul Faiza; Maharani, Lisa; Masita , Nurul Aisatul (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study is a literature review in the field of career and industrial counseling. The purpose of this research is to examine major theories in career counseling, particularly the theories proposed by John L. Holland, Donald E. Super, and John D. Krumboltz. The research employed a qualitative descriptive method using a library research design. Data were collected from various academic sources, including scientific journals, books, and research reports relevant to career development theories. The findings indicate that three major theories significantly contribute to understanding career development. Holland’s theory emphasizes the congruence between individual personality types and work environments. Super’s theory highlights career development as a lifelong process influenced by self-concept, life span, and life space. Meanwhile, Krumboltz’s social learning theory explains that genetic endowment, environmental conditions, learning experiences, and task-approach skills shape career decision-making processes. By integrating these three perspectives, individuals can better understand and navigate career development in a dynamic and competitive work environment.